Norm as Exclusionary Reason for Action - Hadži Stević, Brano (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2021)
We respect legal rules for various reasons, but Raz believes that rule represents exclusionary reason for action because it is reason that cannot be weighed with other reasons. Thus, there are first-order reasons that can be balanced in order to achieve some practical decision, but there are also second-order reasons that preclude such balancing. Raz’s theory starts from the fact that norms are created by authority whose statements represent (second-order) reasons for action, regardless of their merits and morally acceptability. However, although the norm is valid regardless of its merits, Raz does not deny importance of legitimacy and morality, because he believes that law claims to legitimate moral authority. The first part of the paper is dedicated to Raz’s understanding of the reasons for action, while in the second part the attention is paid to the rules as reasons for action. Their uniqueness is visible even intuitively, and Raz’s views that a rule is a content-independent and exclusive reason for action are especially considered in the paper. The third part of the paper is dedicated to Raz’s understanding of authority and the final assessment - is the norm strong or exclusionary reason for action?